DNA barcodes of Plecoptera from China: The preliminary dataset and its performance in species delimitation - Chen, Zhi-Teng; Jiang, Chao; Li, Yuan-Sen-Yu (Zootaxa, 2020)
The DNA barcodes of Chinese Plecoptera project has a goal to promote species identification, life stage association, systematic, conservation, biodiversity, and population genetic studies for stoneflies of China. In this study, we sequenced and analyzed 19 DNA barcode sequences belonging to 19 stonefly species, increasing the Chinese barcoded stonefly species number to 53. Genetic distances were calculated and the gene trees constructed, suggesting the efficiency of delimiting Chinese stonefly species using DNA barcodes.